Интродукция из Познани в Киев черных дроздов (Turdus merula L.) - Грачик, Р.; Федоренко, А.П.; Лоскот, В.М.; Чуприн, С.Л. (Вестник зоологии, 1975)
In spring 1972 106 young birds of the town population of Turdus merula L. were grown in Poznan and delivered to Kiev by plane (about 1000 km). The birds were set free in the territory of the Zoo. Observations showed that about half of the birds number settled in the areas adjoining the Zoo within a radius of about 5 km. T. merula L. overwintered safely and began reproducing in spring 1973. Three couples of birds which made their nests in the Zoo territory in 1973 gave 28 nestlings. Introduction of T. merula L. town population in Kiev was successful.